Implementasi Program KKN Melalui Pembuatan Lapangan dan Kompetisi Bola Voli Sebagai Upaya Pengembangan Olahraga Masyarakat Kudu Ganting Barat - Setiyo Utoyo; Muhammad Teguh; Agus Ato; Nengsih Surya Putri (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
Community Service Programs (KKN) serve as a platform for students to contribute to the community, aiming to synergize academic knowledge with real-world needs. This article discusses the implementation of the KKN program focused on sports in Nagari Kudu Ganting Barat, V Koto Timur District, Padang Pariaman Regency. The program was realized through two main activities: the construction of a volleyball court and the holding of an inter-village volleyball competition. The deteriorating condition of the volleyball court, damaged by weather, was the primary motivation for this program. Methods employed included direct observation, a participatory approach (Participatory Action Research/PAR), and organizing a competition to encourage social engagement. Results indicate that the field construction—carried out collaboratively with the community—successfully rehabilitated the sports facility, while the inter-village competition increased community spirit and social cohesion. This program demonstrates that interventions focused on local needs, when designed with active community participation, can have a meaningful and sustainable social impact.